2019
DOI: 10.1016/j.paid.2019.05.047
|View full text |Cite
|
Sign up to set email alerts
|

Rumination selectively mediates the association between actual-ideal (but not actual-ought) self-discrepancy and anxious and depressive symptoms

Abstract: Actual-ideal and actual-ought self-discrepancies have been theorised to be independently associated with depressive and anxious symptoms respectively. This study tested this prediction and extended it to consider whether rumination mediates these relationships. One hundred and thirty-eight students (48 males, 90 females) listed four adjectives describing how they would ideally hope to be and four adjectives describing how they ought to be.Participants then rated how distant they perceived themselves to be from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 31 publications
0
13
1
Order By: Relevance
“…Past research also suggests that goal tenacity may be associated with psychopathology and perfectionism, particularly if someone continues to pursue goals that are unrealistic and unattainable [ 21 ]. Further, several studies have associated goal inflexibility with a range of psychological disorders (e.g., depression and anxiety) and maladaptive psychological mechanisms such as negative rumination [ 5 , 23 , 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…Past research also suggests that goal tenacity may be associated with psychopathology and perfectionism, particularly if someone continues to pursue goals that are unrealistic and unattainable [ 21 ]. Further, several studies have associated goal inflexibility with a range of psychological disorders (e.g., depression and anxiety) and maladaptive psychological mechanisms such as negative rumination [ 5 , 23 , 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, actual:ideal discrepancy was more strongly related to both depression and anxiety compared to actual:ought discrepancy (Mason et al, 2019). Although cumulating evidence emphasizes the importance of self-discrepancies for numerous aspects of psychopathology, less is known about variables that might mediate or moderate the relationships between selfdiscrepancies and psychopathology (Dickson et al, 2019;Higgins, 1999;Mason et al, 2019). To discern such patterns, the present research investigates how affective styles and self-efficacy contribute to the relationships between selfdiscrepancies and depression, anxiety, and psychological well-being.…”
Section: Introductionmentioning
confidence: 94%
“…The above-mentioned meta-analysis called for an investigation of different aspects of emotion regulation as important variables implicated in the relationship between self-discrepancies and psychopathology (Mason et al, 2019). Indeed, some recent studies found selective moderation effects for actual:ought discrepancies and emotion regulation on anxiety symptoms (Gürcan-Yıldırım & Gençöz, 2022) and selective mediation effects of rumination on the relationship between actual:ideal discrepancies and depressive and anxious symptoms (Dickson et al, 2019). Altogether, research demonstrates that self-discrepancies may lead to unfolding negative emotional cascades that may require emotional regulation to maintain psychosocial functioning (Mason et al, 2019).…”
Section: Emotion Regulation and Affective Stylesmentioning
confidence: 99%
“…Four dimensions have been identified for the self-concept construct: actual self depicts how a person sees himself or herself; ideal self refers to what a person would like to be; social self describes what one individual believes other people see them as; and ideal social self refers to how one person would like to be considered by other people (Belch and Landon, 1977; Sirgy, 1982). The authors decided to focus on the actual self and ideal self, given their wide recognition in the current marketing research (Malär et al , 2011; Dickson et al , 2019; Rabbanee et al , 2020).…”
Section: Conceptual Model and Hypothesis Developmentmentioning
confidence: 99%